Principles-Based Securities Regulation in the Wake of the Global Financial Crisis - Ford, Cristie (McGill Law Journal / Revue de droit de McGill, 2010)
The recent global financial crisis contains cautionary lessons about the risks associated with principles-based regulation when it is not reinforced by an effective regulatory presence. Our response to the crisis, however, should not be a rush to enact more rules-based regulatory approaches. On the contrary, principles-based securities regulation offers more viable solutions to the challenges that such a crisis presents for contemporary financial markets regulation.The author draws on the lesson of the global financial crisis to identify three critical factors for effective principles-based securities regulation. First, regulators must have the necessary capacity in terms of numbers, access to information, and expertise in order to act as an effective counterweight to industry. Second, regulation needs to grapple with the impact of complexity on financial markets and their regulation. Third, increased diversity among regulators and greater independence from industry are required to avoid conflicts of interest, overreliance on market discipline, and “groupthink”. The paper calls for a continuing commitment to principles-based regulation, accompanied by meaningful enforcement and oversight.